Beampattern analysis of frequency diverse array radar: a review - Zeeshan Ahmad; Meng Chen; Shu-Di Bao (EURASIP Journal on Wireless Communications and Networking, 2021)
Abstract Electronic beam steering is an essential feature of state-of-the-art radar systems. Conventional phased array (PA) radars with fixed carrier frequencies are well-known for electronically steering their beam with high directivity. However, the resulting beampattern is angle-dependent but range-independent. Recently, a new electronic beam steering concept, referred to as frequency diverse array (FDA) radar, has attracted increasing attention due to its unique range-angle dependent beampattern. More importantly, the FDA radar employs a small frequency increment across the array elements to achieve beam steering as a function of angle, range, and time. In this paper, we review the development of the FDA radar since its inception in 2006. Since the frequency offset attaches great importance in FDAs to determine the beampattern shape, initially much of the research and development were focused on designing the optimal frequency offsets for improved beampattern synthesis. Specifically, we analyze characteristics of the FDA beampattern synthesis using various frequency offsets. In addition to analyzing the FDA beampattern characteristics, this study also focuses on the neglected propagation process of the transmitted signals in the early FDA literature, and discuss the time-variant perspective of FDA beampatterns. Furthermore, FDA can also play a significant role in wireless communications, owing to its potential advantages over the conventional PAs. Therefore, we highlight its potential applications in wireless communication systems. Numerical simulations are implemented to illustrate the FDA beampattern characteristics with various frequency offset functions.